Retroviral marking of human bone marrow fibroblasts: in vitro expansion and localization in calvarial sites after subcutaneous transplantation in vivo. - Oreffo, R; Virdi, A; Triffitt, J (2001)
Amplification of multipotential stem cells, with or without ex vivo gene transfer, offers the potential for their use for beneficial repopulation of a host in which there is specific cellular deficiency or functional impairment. The aims of the current study were to immunoselect, genetically mark, and determine the fate of fibroblastic progenitor cells in vivo. A monoclonal antibody, HOP-26, which has high reactivity with a cell surface antigen present on human osteoprogenitors in bone marrow fibroblast populations, was used to select these cells by immunopanning. Following culture in 10% FCS in alphaMEM containing ascorbate-2-phosphate and dexamethasone the amplified cells expressed the osteoblast phenotype as determined by expression of osteocalcin protein determined immunohistochemically, and Type I collagen and osteocalcin mRNA expressions determined by RT-PCR analysis. The selected cells were genetically labeled using a murine leukemia virus (MuLV) encoding a reporter gene (lacZ) with a selective marker gene (neo(r)) using a triple transient transfection protocol. Transfected cells were implanted in CB17 scid/scid mice by local subcutaneous injection over the calvariae. Localization of the genetically marked cells within the calvarial tissues was detected by beta-galactosidase histochemistry and immunocytochemistry. Genetically marked cells were observed within the periosteal layer in close association with the osteoblast layer, covering mineralized bone surfaces and within bone osteoid at 5 and 7 days after injection. This study demonstrates the successful selection, expansion, and retroviral-marking of human osteoprogenitors and their migration and localization within calvariae of SCID mice following in vivo implantation. These basic studies indicate the migration of these cells to skeletal sites and support possibilities for future uses of human osteoprogenitors in therapy of bone deficiency diseases and the potential for development of gene therapy procedures in these conditions.